Delays in Protection Devices and Their Effects on Selectivity: The Reaction Time Gap - Gehring, Johannes; Schwanninger, Raffael; Drexler, Kilian; Wunder, Bernd; Lorentz, Vincent R. H.; März, Martin (2026)
This Paper investigates how the internal delays of a circuit breaker until the limitation of the fault current affect the selectivity of a LVDC-grid under short-circuit condition. It therefore focuses on the tripping characteristics and fundamental processes leading to these delays. Experimental short-circuit tests verify non-selective behavior occurring with high current slopes. To describe this effect, the reaction time gap is introduced. It describes the delay between the time when the circuit breaker should ideally trip immediately after detecting the fault and the time when it actually does so. Therefore, the underlying timing for the tripping of circuit breakers is discussed. Measurements with different circuit breakers prove the reaction time gap and show large variations in selectivity margins. Possible countermeasures to overcome the reaction time gap relating to the behavior of the grid and the circuit breaker are outline
https://cris.fau.de/converis/publicweb/Publication/355471836